Increased intake of marine fish contributed to a decreased odds of comorbid depressive symptoms and coronary heart disease in Chinese adults - Fan, Yuncao; Chen, Wei; Lin, Wenhui; Jin, Jungu; Lou, Enyu; Lao, Jiaying; Chen, Yu-Hsin; Shao, Jianzhi; Wang, Qizeng; Jiang, Qingxi; Wang, Fan; Xu, Jinzhong; et al. (Frontiers in Nutrition, 2025)
BackgroundsIncreased consumption of fish has beneficial impacts upon emotional health; however, this benefit for comorbid depressive symptoms and coronary heart disease (DCHD) is not fully clear. We aimed to investigate the relationship between consumption of marine fish and DCHD in Chinese adults.MethodsA cross-sectional study was conducted in 1,106 participants aged 25–95 years living in Taizhou, China. Fish intakes were assessed by using a validated food frequency questionnaire, with their tertiles as category levels of ≤1 time/week, 2–6 times/week, and ≥7 times/week. Coronary heart disease (CHD) was diagnosed using the coronary angiography, while the concurrent depressive symptoms was indicated using ≥8 scores from hospital anxiety and depression scales (HADS). Primary measurements were the prevalent DCHD, presented as multivariate-adjusted odds ratios (ORs) with 95% confidence intervals (CIs).ResultsA total of 932 participants were included, 88 (9.44%) participants with depressive symptoms, 477 (51.18%) CHD, and 106 (11.37%) DCHD, respectively. Participants at the highest tertile of fish intake have a lower odds of DCHD compared with those at the lowest (OR: 0.34, 95% CI: 0.20, 0.58), with 42% reductions in odds of DCHD for per one-tertile (3 times/week) increase (OR: 0.58, 95% CI: 0.45, 0.76). The beneficial associations were pronounced with decreased odds of depressive symptom (OR: 0.31, 95% CI: 0.20, 0.47), but not with CHD (OR: 0.87, 95% CI: 0.59, 1.29).ConclusionsIncreased consumption of marine fish is associated with decreased severity of depressive symptoms, which might have great benefits toward comorbid depressive symptom and with coronary heart diseases.